Medical image processing and analysis of MRI images for Sarcopenia detection - Goh, Ying Hong (2016)
Sarcopenia is characterized as the degenerative loss of muscle mass and function and it is associated with several major age-related clinical conditions. The reduction in muscle size could be characterized by the replacement of muscle fibers with fats and is systematically occurring throughout the skeletal muscles with different extent and velocity affecting the muscle function and mobility performance. The project aims to study the pattern of fat infiltrations and identify the correlation of the skeletal muscle and fat composition with CSHA clinical frailty scale through a quantitative analysis based on the MRI images. The study focus on the muscle group along the patella which were more susceptible to age related atrophy. The statistical difference were observed in the intramuscular fat volume and fat density between the CSHA groups and normal young patient between the ages of 20 – 30 years old. These differences suggested that composition of intramuscular fats and fat density in the body could potentially help identify the level of frailty and sarcopenia of the patient. The texture of the muscle were also significantly different between the CSHA groups and normal young patient between the ages of 20 – 30 years old.